(untitled) (Revista de Crítica Literaria Latinoamericana, 2023)
In recent years, we have witnessed an intense elaboration of documents and documentary materials in Latin American art practices. Artists have engaged in a critical interrogation of the means of representation and on the status of the “document” as such. A tendency to staging reality blends documentary materials with fiction and an exhibition of “lived” experience. Although this article will concentrate only in two Latin American dramatic works—Campo Minado, by Lola Arias (2016) and El rumor del incendio (2010) by the collective Lagartijas tiradas al sol—it aims to discuss in a more general sense the documentary thrust in contemporary Latin American cultural practices.